Sistem Ar Drone Pengikut Garis Menggunakan Algoritma Progressive Probabilistic Hough Transform - Achmad Baichuni Zain; Gembong Edhi Setyawan; Hurriyatul Fitriyah (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Quadcopter is UAV which has four motorcycle propellers used to move it. We can control quadcopter with smartphone or remote control while it is flying, but with a particular skill. Based on the issues, quadcopter should be developed in order to move and follow an object automatically. Quadcopter will detect and follow a black line directly. In this research, we use digital image processing that use canny detection and progressive probabilistic hough transform. Parrot AR Drone 2.0 is used in this research of quadcopter. Based on the result of research, it obtains the point of HSV from each parameter that is Hue with minimum point = 0 and maximum point = 180, Saturation with minimum point = 0 and maximum point = 255, and Value with minimum point = 0 and maximum point = 10. While the measure of frame used for detecting is 330*240 pixel and the percentage of precision of motion is 100 %. The system produces a delay that follows the line in the detected line to quadcopter and the point is 0,22 second. While altitude testing obtain the result that minimum high can be detected is 80 cm and maximum high is 230 cm.